Proceedings Tenth International Conference on Computer Communications and Networks (Cat. No.01EX495)
DOI: 10.1109/icccn.2001.956234
|View full text |Cite
|
Sign up to set email alerts
|

On design and evaluation of "intention-driven" ICMP traceback

Abstract: IONSince late 1999, DDoS (Distributed Denial of Service) [1,2,3] attack has drawn many attentions from both research and industry communities. Many potential solutions (e.g., ingress filtering [6,7], packet marking [5,8,9,10,11] or tracing [4], and aggregate-based congestion control or rate limiting) have been proposed to handle this network bandwidth consumption attack. Among them, "ICMP traceback (iTrace)" is currently being considered as an industry standard by IETF (Internet Engineering Task Force). While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0
7

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(78 citation statements)
references
References 4 publications
0
71
0
7
Order By: Relevance
“…This approach has been extended by Song and Perrig to improve the reconstruction of paths and authenticate the encodings [12]. In order to avoid the backwards compatibility issues and increased computation re-quired by the sophisticated encoding schemes employed in the packet marking schemes, Bellovin's scheme (and later "intentional" extension [13]) simply sends the audit information in an ICMP message.…”
Section: A End-host Storagementioning
confidence: 99%
“…This approach has been extended by Song and Perrig to improve the reconstruction of paths and authenticate the encodings [12]. In order to avoid the backwards compatibility issues and increased computation re-quired by the sophisticated encoding schemes employed in the packet marking schemes, Bellovin's scheme (and later "intentional" extension [13]) simply sends the audit information in an ICMP message.…”
Section: A End-host Storagementioning
confidence: 99%
“…Bellovin et al suggested adding a new type of ICMP message for traceback [25], [26], and Mankin et al present an improvement to this scheme [27]. Several researchers propose to embed traceback information within the IP packet [28], [29], [30], [31], [32], [33], [34], [35], [36].…”
Section: Background and Related Workmentioning
confidence: 99%
“…The Time To Live (TTL) field is then used to identify the actual path depth of the attack. Based on packet messaging, there are some variants proposed: intension-driven iTrace [40] and iCaddie ICMP [41].…”
Section: Traceback With Packet Messagingmentioning
confidence: 99%